Untranslatability is a myth - Mambambo, John (Midlands State University, 2015)
The tower of Babel is the most celebrated Judeo-Christian myth explaining the rationale behind an array of languages spoken on the face of the earth. In colonial and neo-colonial Africa, technical knowledge has been assumed as naturally constructed in the European and Western languages. The flip side of this attitude is that African languages by their nature cannot incorporate knowledge and modern science and cannot be used to teach and learn Science subjects since English is "untranslatable". This study seeks to expose the fallacy behind "untranslatability" by using practical examples from a bilingual Shona-English dictionary entitled Duramazwi reUrapi noUtano hence proving the linguistic property of language called immense complexity.